Role of heart fatty acid binding protein in early detection of non ST-elevation myocardial infarct and its comparison with other cardiac markers - Syed Muhammad Salman Habib; Abdul Rasheed Khan; Sultana Habib; Syed Zia Ullah; Riffat Sultana; Qazi Daniyal Tariq; M. Aslam Zardari; Atiya imdad (Journal of the Pakistan Medical Association, 2020)
Objectives: To determine the role of heart fatty acid-binding protein in early detection of non-ST-elevation myocardial infarction and its comparison with two other cardiac markers. Methods: The cross-sectional study was conducted at Abbasi Shaheed Hospital, Karachi, from June 2012 to June 2014, and comprised patients presenting at the emergency department within two hours of chest pain and who were subsequently referred to the cardiology department with a provisional diagnosis of either unstable angina or non-ST-elevation myocardial infarction. Relevant history was taken on a specific proforma and electrocardiogram as well as routine investigations were done in the emergency department. Blood samples from the subjects were tested for the diagnosis of myocardial infarction through detection of heart fatty acid-binding protein, Troponin-I and Creatine kinase-myocardial band. Sensitivity and specificity of the three markers were calculated keeping coronary angiography as the gold standard. Data was analysed using SPSS 17. Results: Out of 250 patients, 153(61.2%) were males. The overall mean age was 54.45±13.92 years. Sensitivity and specificity of heart fatty acid-binding protein were 80.6% and 78.5% (p<0.05), for Troponin-I, 37.7% and 75% (p>0.05), and for Creatine Kinase-myocardial band, 29.5% and 67.8% (p>0.05). Conclusion: Heart fatty acid-binding protein was found to be a good diagnostic tool for the detection of non-ST-elevation myocardial infarction. Key Words: Non ST-elevation myocardial infarct, Cardiac markers, Heart fatty acid-binding protein, Troponin-I, Creatine kinase isoenzyme MB, Angiography. Continuous...